Midnight - McCulloch, Amy, 1986- (Doubleday, 2024)
"While on a dream cruise aboard a luxury liner to Antarctica, actuary Olivia Campbell is plunged into a desperate battle for survival against a killer determined to stop the ship from reaching its final destination, soon discovering she may have booked a one-way ticket to her own death"--